Analisis Nilai Pendidikan Karakter dalam Novel Bidadari Bermata Bening Karya Habiburrahman El Shirazy - Nurul Azmi; Mukhlis Mukhlis; Saadiah Saadiah (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This study entitled, " Analysis of the value of character education in Bidadari Bermata Bening novels by habiburrahman el shirazy". In accordance with the problem determined, the purpose of this study was to describe the values of character education contained and the value of dominant character education used in the novel of the Bidadari Bermata Bening by Habiburrahman El Shirazy. The source of this research data is the Bidadari Bermata Bening novel by Habiburrahman El Shirazy which consists of 337 pages consisting of 17 sections. The method used in this research is descriptive method with a qualitative approach. The research technique used is document review. The results showed that the values of character education contained in the Bidadari Bermata Bening novel were religious values, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the country, respect for achievement, friendliness or communicative, peace-loving, fond of reading, caring for the environment, social care, and responsibility. The value of dominant character education in this novel is the value of religious character.